Ambrogio e la condanna degli eretici: In difesa della semplicità e dell'unità della fede - Banna, Pierluigi (La scuola cattolica, 2025)
St Ambrose of Milan is traditionally represented as the persecutor of the heretics, in particular of the Arians. In this contribution, seeking to bear in mind the cultural elements which have brought the consolidation of this image of the Bishop of Milan (politics, romanitas, rhetoric, stereotypes of the tradition), we seek of bring to the fore the theological-pastoral criteria which have motivated the presentation, the evaluation and the condemnation of the heresy by the Milanese pastor. With some of these criteria it is still possible to make a comparison today in order to deal with the disagreement within the Church: the search for the orthodoxy as a middle way between extremes, the non unilaterality of the positions for the defense of Church unity, the care of the experience of salvation and the simplicity of the faith.